From waste to managed waste facility and compost for farming: The role of women movement in urban villages in Bali, Indonesia - Utomo, Marcellinus Mandira Budi; Pieter, Levina Augusta Geraldine; Kusumawati, Dewi; Putra, Hermitianta P. (National Research and Innovation Agency, Indonesia, 2023)
One of the problems faced by urban areas is waste, including in Pejeng Village, Bali, Indonesia. With the issuance of Governor Regulation No. 47 of 2019, waste management must be carried out at the village level through waste management facilities (TPS3R) and Pejeng is one of the villages that has successfully implemented this regulation. With so many TPS3R failing halfway, the study of the success factors of TPS3R in Pejeng is important, so that its findings can be a recommendation for possible factors so that TPS3R is successful in other villages. Through field observations, in-depth interviews with key informants, and participatory action research (PAR), it was found that the role of the Pejeng Village women’s organization ‘Laskar Pertiwi’, who voluntarily set aside their time in the waste management movement, has a very large role in educating residents to carry out waste sorting at the household level and never giving up despite many rejections in the early stages of the program, go directly to the field to collect waste and process organic waste into compost for soil improvement materials for agriculture. Through PAR purchasing compost from TPS3R Pejeng and providing compost grants to rice farmers in one planting season as a stimulus to switch from non-organic to organic farming, it is known that there are still compost sales challenges because making rice farmers aware of how to consistently farm organic rice still takes time. Nevertheless, Laskar Pertiwi has succeeded in creating a healthier living environment, waste that has a selling value, and increased public awareness.